A QSPR-approach to the estimation of the pK(HB) of six-membered nitrogen-heterocycles using quantum mechanically derived descriptors - Hennemann, Matthias; Clark, Timothy (Journal of Molecular Modeling, 2002)
Descriptors derived from semiempirical (AM1) molecular orbital calculations have been used to construct a quantitative structure-property relationship (QSPR) for the thermodynamic hydrogen-bond basicity, pK(HB), of a series of six-membered aromatic nitrogen-heterocycles. The resulting model uses four-descriptors (the Coulson charge on the nitrogen atom, the energy of the localized nitrogen lone-pair orbital, the p-orbital contribution to this MO and an accessibility angle). The model gives r(cv)(2)=0.95 for 51 compounds with a standard deviation between calculation and experiment of 0.13 log units.
Keywords: pK(HB); hydrogen bonding; QSPR; AM1